Methods of facing intellectual deviation of youth, proposal from the perspective of cognitive Behavioral Therapy - Al-Enezi, Aminah Mohareb Hizan (Journal of Humanities & Social Sciences, 2021)
The study aimed to identify the aspects of intellectual deviation among youth and review the causes and motives behind such deviation to develop a proposal from the perspective of Cognitive Behavioral Therapy (CBT). This study is descriptive and it depends on the descriptive-analytical method. The researcher used the simple random sample of faculty members in the Department of Sociology and Social Service: Department of Sociology and Social Service at Imam Muhammad bin Saud Islamic University, the Department of Social Service at Princess Nora University, and the Department of Social Sciences at Naif Arab University for Security Sciences with (95) faculty members. The study used the questionnaire as a tool to obtain responses from the sample members. The study came out with a set of results, the most prominent of which were: All faculty members are completely in agreement about the manifestations of intellectual deviation among young people, the most important of which (the audacity to fatwa without science, intellectual closure, and the tendency to justify unreasonably deviant behaviors, rebellion against the religious and moral values ​​of society, and the intolerance of a group , Sect, or sect), and the relative weight of the approval score was (88.1%). The results also indicated several methods to confront intellectual deviation, one of the most important of which is cognitive methods, which is to activate the role of educational institutions in enhancing the confidence of young people themselves, and to address the negative aspects of globalization among young people, and the relative weight of the approval score was (96.1%). Also, one of the most important methods of facing intellectual deviation was the behavioral methods represented in urging young people to contribute to voluntary work, and helping young people to choose sound behavioral example, and the relative weight of the approval score was (95.1%). In light of the previous results, the study recommended the necessity for the family to develop a sense of loyalty and belonging to the country, obedience to the rulers, respect for security men, and avoiding extremism among its members, especially young people.